2005
DOI: 10.1103/physreve.71.011501
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency longitudinal and transverse dynamics in water

Abstract: High-resolution, inelastic x-ray scattering measurements of the dynamic structure factor S(Q, ω) of liquid water have been performed for wave vectors Q between 4 and 30 nm −1 in distinctly different thermodynamic conditions (T= 263 -420 K ; at, or close to, ambient pressure and at P = 2 kbar). In agreement with previous inelastic x-ray and neutron studies, the presence of two inelastic contributions (one dispersing with Q and the other almost non-dispersive) is confirmed.The study of their temperature-and Q-de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
119
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 37 publications
12
119
0
Order By: Relevance
“…As already observed in other experiments performed in this Qrange [6][7][8][9][20][21][22], we found that the value of τ α (Q) decreases with increasing Q at a given temperature. As an example we report the Q-dependence of such a parameter for two selected temperatures in the inset of fig.3.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…As already observed in other experiments performed in this Qrange [6][7][8][9][20][21][22], we found that the value of τ α (Q) decreases with increasing Q at a given temperature. As an example we report the Q-dependence of such a parameter for two selected temperatures in the inset of fig.3.…”
Section: Resultssupporting
confidence: 90%
“…As a consequence the corresponding term in the memory function can be approximated by a δ(t)-function [7,8]. The second exponential term in eq.2 accounts for the visco-elastic transition responsible for the positive sound dispersion.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[77,78]), transverse modes have been later studied in low-viscous liquids on the basis of positive dispersion [64][65][66]68] (recall our previous discussion that the presence of high-frequency transverse modes increases sound velocity from the hydrodynamic to the solid-like value). These studies included water [79], where it was found that the onset of transverse excitations coincides with the inverse of liquid relaxation time [80], as predicted by (11). More recently, transverse modes in liquids were directly measured in the form of distinct dispersion branches and verified on the basis of computer modeling [69][70][71][72][73].…”
Section: Experimental Evidence For High-frequency Collective Modes Inmentioning
confidence: 99%
“…Correspondingly, there exists a frequency Ω o = 1/τ that marks the transition between a liquid-like behavior (ω < Ω o ) and a solid-like one (ω > Ω o ). In the latter regime, the system has an increased sound velocity ("fast sound") and supports transverse excitations (dispersionless branch) [23]. Both the fast sound and the existence of a second branch, therefore, got their ultimate origin from the existence of a structural relaxation process.…”
Section: The Early Ixs Measurementsmentioning
confidence: 99%